Antiretroviral therapy in HIV-1-infected individuals with CD4 count below 100 cells/mm3 results in differential recovery of monocyte activation. - Patro, Sean C; Azzoni, Livio; Joseph, Jocelin; Fair, Matthew G; Sierra-Madero, Juan G; Rassool, Mohammed S; Sanne, Ian; Montaner, Luis J (Journal of leukocyte biology, 2015)
Reversal of monocyte and macrophage activation and the relationship to viral suppression and T cell activation are unknown in patients with advanced HIV-1 infection, initiating antiretroviral therapy. This study aimed to determine whether reduction in biomarkers of monocyte and macrophage activation would be reduced in conjunction with viral suppression and resolution of T cell activation. Furthermore, we hypothesized that the addition of CCR5 antagonism (by maraviroc) would mediate greater reduction of monocyte/macrophage activation markers than suppressive antiretroviral therapy alone. In the CCR5 antagonism to decrease the incidence of immune reconstitution inflammatory syndrome study, antiretroviral therapy-naïve patients received maraviroc or placebo in addition to standard antiretroviral therapy. PBMCs and plasma from 65 patients were assessed during 24 wk of antiretroviral therapy for biomarkers of monocyte and macrophage activation. Markers of monocyte and macrophage activation were reduced significantly by 24 wk, including CD14(++)CD16(+) intermediate monocytes (P < 0.0001), surface CD163 (P = 0.0004), CD169 (P < 0.0001), tetherin (P = 0.0153), and soluble CD163 (P < 0.0001). A change in CD38(+), HLA-DR(+) CD8 T cells was associated with changes in CD169 and tetherin expression. Maraviroc did not affect biomarkers of monocyte/macrophage activation but resulted in greater percentages of CCR5-positive monocytes in PBMC. HIV-1 suppression after 24 wk of antiretroviral therapy, with or without maraviroc, demonstrates robust recovery in monocyte subset activation markers, whereas soluble markers of activation demonstrate minimal decrease, qualitatively differentiating markers of monocyte/macrophage activation in advanced disease.